Crystal structure of Isthmin-1 and reassessment of its functional role in pre-adipocyte signaling - Tongqing Li; Steven E. Stayrook; Wenxue Li; Yueyue Wang; Hengyi Li; Jianan Zhang; Yansheng Liu; Daryl E. Klein (Nature Communications)
Abstract Isthmin-1 (ISM1) is a recently described adipokine with insulin-like properties that can control hyperglycemia and liver steatosis. Additionally, ISM1 is proposed to play critical roles in patterning, angiogenesis, vascular permeability, and apoptosis. A key feature of ISM1 is its AMOP (adhesion-associated domain in MUC4 (Mucin-4) and other proteins) domain which is essential for many of its functions. However, the molecular details of AMOP domains remain elusive as there are no descriptions of their structure. Here we determined the crystal structure of ISM1 including its thrombospondin type I repeat (TSR) and AMOP domain. Interestingly, ISM1’s AMOP domain exhibits a distinct fold with similarities to bacterial streptavidin. When comparing our structure to predicted structures of other AMOP domains, we observed that while the core streptavidin-like barrel is conserved, the surface helices and loops vary greatly. Thus, the AMOP domain fold allows for structural plasticity that may underpin its diverse functions. Furthermore, and contrary to prior studies, we show that highly purified ISM1 does not stimulate AKT phosphorylation on 3T3-F442A pre-adipocytes. Rather, we find that co-purifying growth factors are responsible for this activity. Together, our data reveal the structure and clarify functional studies of this enigmatic protein.